2019
DOI: 10.1007/s10340-019-01103-x
|View full text |Cite
|
Sign up to set email alerts
|

Supplementary UV radiation on eggplants indirectly deters Bemisia tabaci settlement without altering the predatory orientation of their biological control agents Nesidiocoris tenuis and Sphaerophoria rueppellii

Abstract: Ultraviolet (UV) radiation that reaches the earth surface has increased substantially in the past decades, altering insect-plant interactions by directly affecting herbivores behavior or indirectly by modifying plant chemistry and morphogenesis. We evaluated the indirect effect of supplementary UV radiation under glasshouse conditions on Bemisia tabaci settlement, eggplant (Solanum melongena L.) production and its effects on the flight activity of Nesidiocoris tenuis and Sphaerophoria rueppellii. Eggplants wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 69 publications
0
6
0
Order By: Relevance
“…Most natural UV light does not penetrate the glass of greenhouses, but may be supplied by UV LEDs. Even though UV-B can be harmful to plants as a result to DNA damage and ROS production, small doses of UV-B can improve plant defense [66][67][68][69]. Multiple studies show that low doses of UV-B light increase both basal JA and SA levels as well as the basal expression level of several defense-related genes [70].…”
Section: Effects Of Uv-b On Phytohormone-mediated Defensementioning
confidence: 99%
“…Most natural UV light does not penetrate the glass of greenhouses, but may be supplied by UV LEDs. Even though UV-B can be harmful to plants as a result to DNA damage and ROS production, small doses of UV-B can improve plant defense [66][67][68][69]. Multiple studies show that low doses of UV-B light increase both basal JA and SA levels as well as the basal expression level of several defense-related genes [70].…”
Section: Effects Of Uv-b On Phytohormone-mediated Defensementioning
confidence: 99%
“…Experiments showed that the average number of syrphid eggs per plant and the abundance of syrphid larvae was remarkably higher under the photo selective meshes than under the standard coverage. The effect of supplementary UV radiation under glasshouse conditions was also studied, not affecting on the flight activity of adult syrphids [13], but showing that the use of these meshes, and the release of syrphid predators, are compatible strategies to be used in IPM aphid control programs.…”
Section: Hoverflies In Para Biological Control Strategiesmentioning
confidence: 99%
“…Application of UV-B has been observed to have a positive effect on, e.g., basil (Mosadegh et al 2018 ; Nascimento et al 2020 ), rice (Faseela and Puthur 2018 ), chili pepper (Dolzhenko et al 2010 ), mung bean (Wang et al 2017 ), and wheat (Chen et al 2019 ). Besides, UV-B radiation impacts insect-plant interactions, directly by affecting herbivore behavior or indirectly by altering plant biochemistry and morphology (Bornman et al 2019 ; Prieto-Ruiz et al 2019 ). In addition, the use of light-emitting diode (LED) illumination in the horticultural field is constantly expanding.…”
Section: Introductionmentioning
confidence: 99%